2021
DOI: 10.3847/1538-4357/ac13ac
|View full text |Cite
|
Sign up to set email alerts
|

A Catalog of Potential Post–Common Envelope Binaries

Abstract: We present a catalog containing 839 candidate post–common envelope systems. Common envelope evolution is very important in stellar astrophysics, particularly in the context of very compact and short-period binaries, including cataclysmic variables, as progenitors of, e.g., supernovae Type Ia or mergers of black holes and/or neutron stars. At the same time, it is a barely understood process in binary evolution. Due to limitations, since partially remedied, on direct simulation, early investigations were mainly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 497 publications
0
36
0
Order By: Relevance
“…panions are known (e.g., Hernández Santisteban et al 2016;Kruckow et al 2021) but these systems cannot be used to constrain CE evolution as the mass transfer history and therefore the initial mass of the secondary can neither theoretically nor observationally be determined.…”
Section: Systems Not Included In Our Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…panions are known (e.g., Hernández Santisteban et al 2016;Kruckow et al 2021) but these systems cannot be used to constrain CE evolution as the mass transfer history and therefore the initial mass of the secondary can neither theoretically nor observationally be determined.…”
Section: Systems Not Included In Our Reconstructionmentioning
confidence: 99%
“…The first detection of a PCEB containing a BD in close orbit around a WD was presented by Maxted et al (2006) and today a dozen such systems have been suggested (e.g. Van Roestel et al 2021;Kruckow et al 2021). The most useful systems among these binaries are certainly those where the WD is eclipsed by the BD.…”
Section: Introductionmentioning
confidence: 99%
“…Population synthesis studies by Han et al (2002Han et al ( , 2003 identified three main binary channels for forming sdB stars: (i) stable mass transfer (Roche lobe overflow, RLOF) followed by unstable mass transfer and common envelope evolution, (ii) an episode of stable RLOF, and (iii) the merger of two Hecore WDs. The existence of short-period sdB binaries with WD companions, formed in the first channel (i), indicates that the first mass-transfer phase has to be both stable and very nonconservative (Geier 2020;Kruckow et al 2021). The An evolutionary channel for CO-sdOs and He-sdOBVs 3 Hertzsprung-Russell diagram of the evolutionary sequences computed for our "toy merger" model.…”
Section: The Evolutionary Scenariomentioning
confidence: 88%
“…Still these examples highlight the need for the first mass transfer event to be very non-conservative as found by Han et al (2002). Despite the possible theoretical complications to explain the loss of angular momentum, we know from observations that these compact systems composed of a low-mass hot subdwarf with a low-mass WD companion exist (Geier 2020;Kruckow et al 2021).…”
Section: The Evolutionary Scenariomentioning
confidence: 99%
“…The recent catalogue of post common enevlope binaries of Kruckow et al (2021) lists five white dwarf, sdB binaries with an orbital period shorter than 80 min: OW J0815-3421 is now the sixth such binary. The mass of the component stars are similar to ZTF J2320+3750 (55.25 min) (Burdge et al 2020a) and ZTF J2055+4651 (56.35 min) (Kupfer et al 2020).…”
Section: Ow J0815308-3421235mentioning
confidence: 99%